Introduzione alla filosofia dello Stato e della politica di Luigi Sturzo (Stato, Chiese e pluralismo confessionale, 2024)
Introduction to the Luigi Sturzo’s philosophy of state and politicsABSTRACT: The paper offers an introductory overview of the thought of Luigi Sturzo, on the occasion of the 65th anniversary of his death, retracing the essential nodes of his philosophy of the State and politics. The issues addressed by sturzian reflection, in fact, not only stand as paradigmatic for the understanding of the historical phenomena that occurred in the 20th century, but due to their relevance and rationality they are also proposed as tools for understanding the current political and legal reality.SOMMARIO: 1. Introduzione - 2. Il contesto storico - 3. Filosofia dello Stato e della politica di Luigi Sturzo - 3.1 - Crisi dello Stato e democrazia - 3.2 - Stato e statalismo - 3.3 - Partiti e partitocrazia - 4. Conclusioni.